Stock liquidity and dividend payouts in the emerging markets - Bakri, Mohd Ashari (2020)
The stock liquidity and dividend empirically state having a negative relationship in earlier research. However, recent empirical evidence claims that this study neglects the informational effect of stock liquidity and discover contradictory findings in their research relative to the previous study. The mixed findings leave room or gaps to uncover what may strengthen or weaken the relationship, which contributed to the mixed discovery in the previous literature. Furthermore, since an earlier study concentrated in developed markets and a recent study focused on emerging markets, this should leave room to discover how these two significantly different markets may influence this relationship. The study uses a sample from twenty-two (22) emerging market countries for the period of 2006 to 2015, the study aims to achieve three objectives using panel Tobit and panel Logistic regression both with random effect. Firstly, the study examines the nature of the relationship between stock liquidity and dividend payout across emerging market countries. Secondly, the study examines the country level moderating effect, namely financial market development and governance quality on the relationship between stock liquidity and dividend payout. Third, the study investigates the firm-level moderating effect, which is the moderating effect of a family business on the link between stock liquidity and dividend payout. The results reveal that stock liquidity and dividend payout are positively related and consistent with different proxies of liquidity. The first country-level moderating factor, namely financial market development, positively moderates the relationship between stock liquidity and dividend. It indicates that financial market development enhances stock liquidity, mitigates information asymmetry, and increase firm incentives to pay a dividend. In contrast, second country-level moderator, namely governance quality, negatively moderates the relationship between stock liquidity and dividend. Governance quality negatively moderates the relationship between stock liquidity and dividend payout because firms use dividends as a substitute for weak governance, which aligns with substitute hypotheses. Family business as moderator at the firm level shown to have a positive moderating effect on stock liquidity and dividend payout relationships. It indicates that family business reduces dividend payout by positively moderate the negative relationship between stock liquidity and dividend, which initially has a positive relationship without interaction from a family business firm. The study contributes to the literature in two ways. First, the study introduces three new moderating factors on the relationship between stock liquidity and dividend payout. Secondly, unlike past studies, which assume that governance quality should reduce information asymmetry and increasing incentives to pay dividends, and family business should increase information asymmetry and reduce dividend payment, the study found the contrary. This study found that under the condition of weak governance such as in emerging market countries, firms rely on dividends as a substitute for poor governance to maintain good relationships with investors, which results in a negative moderating effect of governance quality. The result also shows that family business reduces dividend payout because family business positively moderates the negative relationship between stock liquidity and dividend, which initially has a positive relationship without the interaction with the family business firm.